Proanthocyanidins in an astringent persimmon inhibit Salmonella pathogenicity island 1 (SPI1) secretion. (1st July 2015) - Morita, Ai; Tai, Akihiro; Ito, Hideyuki; Ganeko, Natsuki; Aizawa, Shin‐Ichi
Abstract: BACKGROUND: Astringent compounds contained in persimmon fruits have been widely used in Japan as food preservatives and thus as anti‐bacterial and anti‐fungi reagents. However, the molecular mechanism of the anti‐microbial activity has been unclear. One of the virulence secretion systems in Salmonella enterica was used to test the anti‐microbial activity of extracts from a persimmon ( Diospyros kaki Thunb 'Saijo'). RESULTS: We found that the extract could inhibit the secretion of virulence proteins but did not affect cell growth and determined the critical concentrations of the extract to show the effect. Then, the effective fraction on the suppression of secretion of virulence proteins was purified from the crude extracts using solvent partition, absorption chromatography and gel filtration chromatography. The anti‐bacterial fraction was analysed by HCl–butanol treatment and gel permeation chromatography followed by nuclear magnetic resonance and identified as the octamers of epigallocatechin and its gallate as major components. CONCLUSION: Proanthocyanidins suppress the secretion of Salmonella pathogenicity island 1 virulence proteins. © 2015 Society of Chemical Industry